Perancangan Karakter Ilustrasi Pada Buku Edukasi Pupuk kompos Dari Sampah Organik : merancang karakter ilustrasi untuk buku edukasi lingkungan - suryani, Eli; Riyanto, Bedjo; Sarwono, Sarwono (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2024)
Waste is a serious problem in Indonesia, including Surakarta City, due to the low awareness of the community, especially housewives, in its management. This design aims to design character illustrations in the educational book of compost fertilizer from organic waste to help deliver information effectively. This design focuses on character illustrations inspired by the head of the PKK women who will be used in the educational book. This type of research is qualitative research with a descriptive approach, the design method used is design thinking. Data collection is done through observation, interviews, questionnaires and documentation. The design thinking method consists of five stages, namely empathize, define, ideate, prototype and testing. The data used in this design consists of library data, data from interviews with PKK leaders and members in Jebres Village. The result of this design is an educational book that has a size of 14.8 cm x 21 cm or A5 size with 33 pages. The type of paper used on the book cover is 260 gsm artcarton while, for the contents using 150 gsm artpaper. Supporting media in this design are posters and Merchandise, namely tote bags and pins. Educational media in the form of books has been tested on the target audience and the character illustrations presented are able to represent educational messages effectively through visualization of friendly characters, familiar with the audience, and costumes that support and pay attention to the appropriate color theory.